2013
DOI: 10.1590/s0036-46652013000400009
|View full text |Cite
|
Sign up to set email alerts
|

Co-Infection of Dengue Virus by Serotypes 1 and 4 in Patient From Medium Sized City From Brazil

Abstract: SUMMARYThe natural co-infection with dengue virus can occur in highly endemic areas where different serotypes have been observed for many years. We report one case of DENV-1/DENV-4 co-infection in human serum detected by molecular tests. Phylogenetic analysis of the sequences obtained indicated the presence of genotype V and II for DENV-1 and DENV-4, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…Some authors have noticed that concurrent infections by different DENV serotypes may increase severity due to increased virus titers and other factors 24 . The absence of a clinical correlation between co-infections and disease outcome has already been reported 8 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Some authors have noticed that concurrent infections by different DENV serotypes may increase severity due to increased virus titers and other factors 24 . The absence of a clinical correlation between co-infections and disease outcome has already been reported 8 .…”
Section: Discussionmentioning
confidence: 93%
“…Co-infections occur naturally and are not necessarily associated with increased disease severity. In Brazil, co-infections by DENV-2/DENV-3 were reported in Taua, in the state of Ceara 2 ; by DENV-2/DENV-4, DENV-1/DENV-2, DENV-1/DENV-4, and DENV-3/DENV-4 in Manaus AM 4 , 24 ; and by DENV-1/DENV-4 in Sao Jose do Rio Preto, SP 8 . Because clinical follow up was not performed in this study, it is not possible to determine whether co-infections resulted in increased disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Co-infection with the serotypes DENV-1/-4 and DENV-2/-4 were observed in Mato Grosso state 41 ; co-infection with DENV-1/-4, in São José do Rio Preto, São Paulo state 42 ; co-infection with DENV-1/-4, DENV-2/-4, DENV-1/-2, and DENV-3/-4, in Manaus, Amazonas state11, 43, 44; co-infection with DENV-2/-3, in Tauá, Ceará state 45 ; co-infection with DENV-1/-2, in Barretos, São Paulo state 46 ; and co-infection with DENV-1/-2, in Cuiabá, Mato Grosso state 47, 48. Co-infections with more than one serotype were also detected in Ae.…”
Section: Denv-4mentioning
confidence: 94%
“…DENV-2, DENV-3, and DENV-4 were detected in 1998, 2005, and 2011, respectively (Mondini et al, 2009;Rocco et al, 2012). Colombo et al (2013) reported the first case of DENV-4 in 2011, simultaneously with the public health authority of the State, which detected this serotype in the same patient. In 2011, DENV-4 was detected co-circulating with the DENV-1 and DENV-2 (Souza et al, 2011), and caused major outbreaks in the next two years.…”
Section: Study Area and Timeframementioning
confidence: 99%